2013
DOI: 10.1007/s00404-013-3090-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of adding metformin in insulin-resistant diabetic pregnant women: a randomized controlled trial

Abstract: Adding metformin to insulin therapy in women with insulin-resistant diabetes mellitus with pregnancy seems to be effective in proper glycemic control in a considerable proportion of women, along with benefits of reduced hospital stay, reduced frequency of maternal hypoglycemia as well as reduced frequency of neonatal hypoglycemia, NICU admission and neonatal respiratory distress syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 24 publications
3
43
0
3
Order By: Relevance
“…We considered α to be 0.05 and chose a power of 95% (β = 0.05), in order to minimize the risk of type II error. The sample size was calculated according to the following equation, a drop‐out rate of 10% was anticipated (slightly higher than the 8.7% rate previously published from our hospital): normalN=normalK×normalD×()normalp1×1normalp1+[]p2×()1p2true/normalp1normalp22 …”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…We considered α to be 0.05 and chose a power of 95% (β = 0.05), in order to minimize the risk of type II error. The sample size was calculated according to the following equation, a drop‐out rate of 10% was anticipated (slightly higher than the 8.7% rate previously published from our hospital): normalN=normalK×normalD×()normalp1×1normalp1+[]p2×()1p2true/normalp1normalp22 …”
Section: Methodssupporting
confidence: 92%
“…study, and 76.1% in the Ibrahim et al . study . Therefore the aim of this study was to determine whether metformin with or without supplemental insulin may be as effective as insulin in controlling blood glucose.…”
Section: Methodsmentioning
confidence: 98%
“…In addition, we did not assess the effects of calcium and vitamin D supplementation on pregnancy outcomes. However, earlier studies have shown that admissions to neonatal intensive care units were significantly reduced when maternal glycaemic control improved [8]. In addition, management of inflammation through administration of anti-inflammatory drugs during pregnancy significantly regulated ambulatory blood pressure and reduced the incidence of pre-eclampsia, gestational hypertension, preterm delivery and intrauterine growth retardation [39].…”
Section: Discussionmentioning
confidence: 99%
“…Current therapies for GDM include a low-glycaemic index diet, carbohydrate restriction [7], the use of some oral hypoglycaemic agents [8] and insulin therapy [9]. A few recent studies have shown that supplementation with calcium [10] and vitamin D [11] in patients with GDM might affect pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Metformin was associated with fewer hypertensive disorders of pregnancy but more small for gestational age infants 61. An additional study by Ibrahim and colleagues of 90 women with gestational diabetes or type 2 diabetes found that the addition of metformin to insulin reduced the risk of neonatal hypoglycemia 60. Several ongoing RCTs comparing metformin with placebo in women with either type 2 diabetes or early onset gestational diabetes receiving insulin (Medical Optimization of Management of Type 2 Diabetes Complicating Pregnancy (MOMPOD), NCT02932475; and Metformin in Women With Type 2 Diabetes in Pregnancy Trial (MiTy), NCT01353391) will provide useful information on the effect of metformin as adjuvant therapy in this population, particularly with regard to the possible reduction in pre-eclampsia rates 67…”
Section: Metforminmentioning
confidence: 99%